A partitioned powder core filament sheet layer positioning hole ceramic composite coating and a preparation method thereof
Patent Information
- Application Number
- CN202611125473.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]针对相关技术的不足,本发明旨在提供一种分区粉芯丝材片层定位成孔陶瓷复合涂层及其制备方法,以解决现有多孔陶瓷复合涂层中成孔组分供料路径不明确、孔隙位置随机性较强以及孔结构与喷涂片层组织对应关系不明确的问题
(1)本发明在丝材横截面上设置相互独立且沿轴向连续延伸的粉料通道,使陶瓷骨架粉末、模板粉末及辅助结合粉末在进入电弧喷涂区前保持物理分隔,降低粉芯内部随机混合对模板相沉积位置的影响。
Smart Images

Figure CN122979808A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a partitioned powder core wire sheet positioning and pore-forming ceramic composite coating and its preparation method, belonging to the field of surface engineering and thermal spraying technology. Background Technology
[0002] Ceramic coatings possess high hardness, wear resistance, corrosion resistance, and heat resistance, making them valuable in applications such as mechanical protection, energy equipment, aerospace, chemical equipment, and thermal protection components. Thermal spraying is a common method for preparing ceramic coatings and metal-ceramic composite coatings. It involves heating, melting, or partially melting the spraying material using a heat source, and then using a high-speed airflow to deposit the sprayed particles onto the substrate surface, forming a coating structure composed of stacked layers.
[0003] In thermal spray coatings, the pore structure affects the coating's thermal insulation, weight reduction, sound absorption, permeability, and interfacial stress relief properties. Related technologies typically employ methods to obtain porous coatings, including adjusting spraying parameters, introducing pore-forming components, post-spray heat treatment, or subsequent phase removal. For arc spraying, powder-cored wires can introduce metals, alloys, ceramics, or other functional components into the spraying material system, thereby preparing metal-based, ceramic-reinforced, or composite functional coatings.
[0004] However, existing lead-wire arc spraying solutions primarily focus on improving the wear resistance, corrosion resistance, or density of the coating through the lead-wire composition, or on forming composite coatings through the material components themselves. For ceramic composite coatings requiring designable pore structures, if relying solely on adjusting spraying parameters or randomly distributing conventional pore-forming components, the correspondence between pore locations and the sprayed layer structure is difficult to control. If relying on the volatilization of low-evaporation-point metals to form pores, the pore-forming process is easily affected by the volatilization, residue, and oxidation behavior of metal components, and it is difficult to stably obtain a pore structure corresponding to the sprayed layer boundaries.
[0005] Therefore, it is necessary to provide a new method for preparing ceramic composite coatings, which enables the pore-forming components to have distinguishable feeding paths and removable characteristics before and after spraying and deposition, and makes the pore formation location correspond to the sprayed sheet deposition structure, thereby obtaining a ceramic composite coating with sheet-positioned pores. Summary of the Invention
[0006] To address the shortcomings of related technologies, this invention aims to provide a partitioned powder core wire sheet-based pore-forming ceramic composite coating and its preparation method, in order to solve the problems of unclear feeding paths of pore-forming components, strong randomness of pore positions, and unclear correspondence between pore structure and sprayed sheet structure in existing porous ceramic composite coatings.
[0007] One objective of this invention is to provide a method for preparing a partitioned powder core wire sheet-type pore-forming ceramic composite coating, specifically including the following steps: (1) The surface of the substrate is roughened to obtain the roughened substrate.
[0008] (2) Using tubular conductive metal as the outer sheath of partitioned powder core wire, an isolation structure is set in the inner cavity of the tubular conductive metal outer sheath, extending continuously along the axial direction of the partitioned powder core wire, forming independent powder channels in the cross-sectional direction of the inner cavity of the tubular conductive metal outer sheath, and filling the different powder channels with ceramic skeleton powder, water-soluble inorganic salt template powder and auxiliary bonding powder respectively to obtain partitioned powder core wire.
[0009] (3) The partitioned core wire is deposited on the roughened substrate surface by electric arc spraying to form a ceramic composite deposition layer containing template phase.
[0010] (4) Selective template removal treatment of the ceramic composite deposition layer containing template phase is carried out in aqueous medium to obtain the ceramic composite deposition layer after selective template removal treatment.
[0011] (5) The ceramic composite deposition layer after selective template removal is subjected to stabilization heat treatment to obtain a partitioned powder core wire sheet positioning pore ceramic composite coating on the substrate surface.
[0012] More preferably, the substrate in step (1) is one of carbon steel, low alloy steel, stainless steel, Ni-based alloy or Co-based alloy; the surface roughening treatment method is one or a combination of sandblasting treatment and mechanical grinding treatment, and the surface roughness Ra of the substrate after roughening treatment is 5~10μm.
[0013] More preferably, the substrate in step (1) is 45 steel; the surface roughening treatment is sandblasting.
[0014] Preferably, in step (2), the outer diameter of the tubular conductive metal outer sheath is 1.6~2.4mm and the wall thickness is 0.15~0.35mm; the tubular conductive metal outer sheath is one of Ni-based alloy, Fe-based alloy, Co-based alloy, stainless steel, NiCr alloy, FeCrAl alloy or NiAl alloy.
[0015] More preferably, in step (2), the tubular conductive metal outer skin has an inner diameter of 0.9~2.1 mm, provided that the inner diameter is equal to the outer diameter minus twice the wall thickness.
[0016] More preferably, the tubular conductive metal outer sheath in step (2) is one of NiCr alloy, FeCrAl alloy or NiAl alloy.
[0017] The partitioning described in this invention refers to dividing the inner cavity of the tubular conductive metal sheath into two or three independent powder channels on the cross-section of the partitioned powder core wire. The isolation structure extends continuously along the axial direction of the wire. This invention does not employ a method of alternating segmented filling of different powders along the length of the wire. The number of powder channels is determined by the types of powder required to maintain independent feeding.
[0018] Preferably, the isolation structure in step (2) is one or more of the following: isolation sheet, isolation rib, isolation tube, multi-cavity partition or rolled partition wall; the isolation structure is made of the same alloy as the tubular conductive metal outer skin, or is made of a metal or alloy that is metallurgically compatible with the tubular conductive metal outer skin.
[0019] More preferably, the isolation structure in step (2) is one of an isolation sheet, an isolation tube, or a multi-cavity partition.
[0020] More preferably, the isolation structure in step (2) forms radial fan-shaped partitions, dual-channel partitions, or concentric annular partitions on the cross-section of the filament, and extends continuously along the axial direction of the partitioned core filament.
[0021] The dual-channel partition is formed by isolation plates connected to the inner wall of a tubular conductive metal outer sheath at both ends. The isolation plates pass through or deviate from the center of the inner cavity of the tubular conductive metal outer sheath, dividing the inner cavity into two powder channels with the same or different cross-sectional areas. The isolation structure extends continuously along the axial direction of the partitioned powder core wire.
[0022] Step (2) of this invention first determines the target filling mass of each powder in a unit length of filament based on the target proportion of each powder, and then determines the required filling volume of each powder by combining the loose packing density and predetermined filling density of each powder. Since the length of each powder channel is the same, the cross-sectional area ratio of the corresponding powder channel is determined by the ratio of the required filling volume of each powder. The cross-sectional area ratio is achieved by adjusting the position of the separator, the included angle between adjacent separators, or the outer diameter of the separator tube, and is verified after powder filling based on the actual amount of each powder added and the actual weight gain per unit length of filament.
[0023] More preferably, in step (2), the bulk density of the ceramic skeleton powder, water-soluble inorganic salt template powder, and auxiliary binding powder is 0.5~6.0 g / cm³. 3The loose packing density is determined using the fixed volume method, i.e., the powder is allowed to naturally fill the powder channel under conditions of no vibration or compaction, and the loose packing density is determined based on the mass of the powder in the powder channel and the volume of the powder channel. The predetermined filling density is expressed using a filling coefficient, which is the ratio of the predetermined packing density of the powder in the powder channel to the loose packing density of the powder, and the filling coefficient is 0.90~1.20. For the i-th type of powder, the required powder channel volume Vi is determined according to Vi=mi / (ρi×Ki), where mi is the target filling mass of the i-th type of powder in the unit length of the partitioned powder core filament, in g, and ρi is the measured loose packing density of the i-th type of powder, in g / cm³. 3 Ki is the filling coefficient of the i-th type of powder, which has no unit, and Vi is the powder channel volume in cm³. 3 The effective cross-sectional area Ai of the corresponding powder channel is determined according to Ai = Vi / L, where L is the length of the unit length partitioned powder core wire in cm, and the effective cross-sectional area Ai of the corresponding powder channel is in cm. 2 Since all powder channels extend to the same length along the axial direction of the wire, the ratio of the effective cross-sectional areas of each powder channel is equal to the ratio of the required powder channel volumes for the corresponding powder. When using two powder channels (divided by partitions), the effective cross-sectional areas on both sides of the partition, after deducting the area occupied by the partition, are adjusted to achieve the required ratio by adjusting the position of the partition relative to the center of the inner cavity. When using three powder channels (divided by partitions using multi-cavity partitions), the effective cross-sectional areas of the three powder channels, after deducting the area occupied by the partitions, are adjusted to achieve the required ratio by adjusting the position of the multi-cavity partitions and the included angle between adjacent partitions. When using concentric annular partitions, the effective cross-sectional areas of the inner powder channel and the outer annular powder channel, after deducting the area occupied by the partition wall, are adjusted to achieve the required ratio by adjusting the inner and outer diameters of the partition tube. After the partition structure is determined, a trial filling of wire of a predetermined length is carried out. The actual amount of each powder added is determined according to the mass difference of the container before and after each powder filling, and the actual filling mass ratio is verified. If there is a deviation, the position of the isolation plate, the position and angle of the multi-cavity partition or the size of the isolation tube are adjusted accordingly, and the trial filling and verification are carried out again.
[0024] More preferably, the auxiliary bonding powder in step (2) is one or more of Ni-based alloy powder, Fe-based alloy powder, Co-based alloy powder, stainless steel powder, NiCr alloy powder, FeCrAl alloy powder or NiAl alloy powder.
[0025] Preferably, in step (2), there are 2 or 3 powder channels; when there are 2 powder channels, the 2 powder channels are filled with ceramic skeleton powder and water-soluble inorganic salt template powder respectively; when there are 3 powder channels, the 3 powder channels are filled with ceramic skeleton powder, auxiliary binding powder and water-soluble inorganic salt template powder respectively.
[0026] More preferably, in step (2), when two powder channels are set, the filling powder is composed of ceramic skeleton powder and water-soluble inorganic salt template powder in a mass ratio of 95:5 to 55:45; when three powder channels are set, the filling powder is composed of ceramic skeleton powder, auxiliary bonding powder and water-soluble inorganic salt template powder in a mass ratio of 70:10:20; the total mass of the filling powder accounts for 15% to 35% of the total mass of the partitioned powder core wire, and the remaining mass is composed of tubular conductive metal outer skin and isolation structure; the particle size of the ceramic skeleton powder is 5 to 100 μm; the particle size of the water-soluble inorganic salt template powder is 5 to 150 μm.
[0027] The effective cross-sectional area of each powder channel is divided as follows: First, based on the target filling mass, measured loose density, and filling coefficient of each powder in the unit length of the powder core wire, the required filling volume of each powder is determined. Since the powder channels extend along the axial direction of the wire at the same length, the ratio of the required filling volumes of each powder is used as the ratio of the target effective cross-sectional areas of the corresponding powder channels. Then, the cross-section of the wire is drawn according to the actual dimensions of the inner diameter of the tubular conductive metal outer sheath and the thickness of the isolation structure, and the effective cross-sectional area of each enclosed powder channel is calculated after deducting the area occupied by the isolation structure. When using two powder channels, first set the separator to pass through the center of the inner cavity. Then, based on the target effective cross-sectional area ratio of the two powder channels, gradually move the separator towards the channel with the smaller area. After each movement, recalculate the effective cross-sectional area on both sides of the separator until the area ratio reaches the target ratio. When using three powder channels, use the center of the inner cavity as the connection point of the three separators. Initially allocate 360° circumferential angles based on the target effective cross-sectional area ratio of the three powder channels. Then, gradually adjust the included angle between adjacent separators and recalculate the effective cross-sectional area of the three channels after deducting the separator area until the target ratio is reached. When using concentric annular partitions, under the condition of a fixed separator wall thickness, calculate the area of the inner channel and the annular channel area between the outer wall of the separator and the inner wall of the conductive metal outer sheath by adjusting the inner and outer diameters of the separator until the two reach the target ratio. The relative deviation between the calculated effective cross-sectional area ratio of each channel and the target effective cross-sectional area ratio shall not exceed 5%. After the partition structure is determined, a trial filling is carried out. The actual amount added is determined based on the mass difference before and after each powder is filled, and the filling mass ratio is verified. When the relative deviation between the actual filling mass ratio and the target mass ratio exceeds 5%, the position of the separator offset, the angle of the separator or the size of the separator tube are adjusted accordingly, and the trial filling and verification are carried out again.
[0028] Preferably, the ceramic skeleton powder in step (2) is one or more of the following: zirconium oxide-based ceramics, rare earth zirconate ceramics, rare earth silicate ceramics, mullite, chromium oxide-based ceramics, or titanium oxide-based ceramics; and the water-soluble inorganic salt template powder is one or more of the following: sodium chloride, potassium chloride, sodium sulfate, or potassium sulfate.
[0029] More preferably, the ceramic skeleton powder in step (2) is one of zirconium oxide-based ceramics, rare earth zirconate ceramics, and rare earth silicate ceramics; the water-soluble inorganic salt template powder is one of sodium chloride, potassium chloride, sodium sulfate, or potassium sulfate.
[0030] In step (2) of this invention, the tubular conductive metal outer skin is used to maintain the conductivity of the wire, continuous feeding and arc melting process, and forms a metal bonding phase after deposition, which is not used as a volatile pore-forming phase.
[0031] Preferably, the conditions for arc spraying in step (3) are: spraying voltage of 25~45V, spraying current of 150~450A, spraying distance of 80~250mm, compressed gas pressure of 0.3~0.8MPa, and wire feeding speed of 2~12m / min.
[0032] The ceramic composite deposition layer containing the template phase in step (3) of this invention includes a ceramic framework phase, a metal bonding phase, and a water-soluble inorganic salt template phase.
[0033] Preferably, the selective template removal process of the aqueous medium in step (4) is one or a combination of aqueous medium soaking, aqueous medium circulation rinsing, aqueous medium ultrasonic assisted elution, or aqueous medium flow elution; the temperature of the selective template removal process is 20~80℃ and the time is 0.5~6h.
[0034] More preferably, the aqueous medium in step (4) is deionized water; when using a circulating rinsing or flowing elution method, the aqueous medium is updated by continuously replenishing fresh deionized water and simultaneously discharging saline aqueous medium.
[0035] Step (4) of this invention, selective template removal, utilizes the difference in solubility of the water-soluble inorganic salt template phase, the ceramic framework phase, and the metal-bound phase in an aqueous medium: after the template phase dissolves, it diffuses outward and is discharged through the lamellar boundaries, pores, and local deposition gaps connected to the outer surface of the coating, while the ceramic framework phase and the metal-bound phase are retained. After the template removal process is completed, energy dispersive spectroscopy (EDS) is used to perform a surface scan of the coating cross-section to detect the characteristic elements Na, K, Cl, or S corresponding to the water-soluble inorganic salt template; when the template characteristic elements are below the detection limit of the detection equipment within the detection area, it is confirmed that the template phase has reached the removal endpoint.
[0036] Preferably, the stabilization heat treatment in step (5) is performed at 600~900℃ for 0.5~3h.
[0037] More preferably, the atmosphere for the stabilization heat treatment in step (5) is air or an inert atmosphere (such as argon atmosphere).
[0038] The ceramic composite coating obtained after stabilization heat treatment includes a ceramic skeleton phase, a metal bonding phase, lamellar positioning pores, and locally connected pores, which are formed by the connection of adjacent lamellar positioning pores.
[0039] Another objective of this invention is to provide a partitioned powder core wire sheet-like pore-forming ceramic composite coating prepared by the method of this invention; the ceramic composite coating includes a ceramic skeleton phase, a tubular conductive metal outer skin, an isolation structure, and a metal bonding phase formed by auxiliary bonding powder, sheet-like positioning pores, and locally connected pores; the sheet-like positioning pores are formed by selective removal of a water-soluble inorganic salt template phase by an aqueous medium, and are distributed at the boundaries of the sprayed sheet and / or in the local deposition area, and the locally connected pores are formed by the connection of adjacent sheet-like positioning pores.
[0040] In step (2) of this invention, after setting an isolation structure that extends continuously along the axial direction of the partitioned powder core wire in the inner cavity of the tubular conductive metal outer skin, the cross-sectional direction of the inner cavity of the tubular conductive metal outer skin forms mutually independent powder channels, wherein neither the tubular conductive metal outer skin nor the isolation structure is used as a volatile pore-forming phase.
[0041] In step (3) of this invention, during the arc spraying process, the isolation structure melts and enters the metal bonding phase in the ceramic composite deposition layer.
[0042] The water-soluble inorganic salt template powder in step (3) of this invention is retained in the ceramic composite deposition layer after deposition and is distributed along the boundary of the sprayed sheet and / or the local deposition area.
[0043] After the selective template removal treatment of the aqueous medium in step (4) of this invention, the template phase is removed from the boundary of the sprayed sheet and / or the local deposition area, and a sheet positioning pore is formed at the corresponding position.
[0044] In step (5) of this invention, the partitioned powder core wire sheet positioning and pore-forming ceramic composite coating after stabilization heat treatment has a ceramic skeleton phase, a metal bonding phase and a sheet positioning pore structure.
[0045] The beneficial effects of this invention are: (1) The present invention sets up independent powder channels that extend continuously along the axial direction on the cross-section of the wire material, so that the ceramic skeleton powder, template powder and auxiliary bonding powder are physically separated before entering the arc spraying zone, thereby reducing the influence of random mixing inside the powder core on the deposition position of the template phase.
[0046] (2) The conductive metal outer skin and the isolation structure are used for conduction, wire feeding and forming metal bonding phase, and are not used as volatile pore-forming phase; the pores are formed by selective removal of water-soluble inorganic salt template phase, avoiding component residue and process fluctuation caused by reliance on low evaporation point metal volatilization.
[0047] (3) The template phase is retained at the boundary of the sprayed sheet and / or in the local deposition area after spraying deposition. After being removed by the aqueous medium, it forms sheet positioning pores and local interconnecting pores corresponding to the sheet deposition structure. The cross-sectional structure diagram of the coating is shown in the figure. Figure 2 As shown.
[0048] (4) The present invention obtains a layered positioning pore structure with different distribution positions, pore size ranges and connectivity by means of the powder channel position and cross-sectional area ratio, template powder filling ratio and particle size, spraying parameters and template removal conditions.
[0049] (5) The present invention combines zoned material supply, retention of template phase along the boundary of sprayed sheet and / or local deposition area and subsequent selective removal to make the pore formation location correspond to the deposition structure of arc sprayed sheet. The resulting coating includes ceramic skeleton phase, metal bonding phase, sheet positioning pores and local interconnecting pores. Attached Figure Description
[0050] Figure 1 This is a flowchart illustrating the preparation process of the partitioned powder core wire sheet layer positioning pore-forming ceramic composite coating of the present invention.
[0051] Figure 2 This is a schematic cross-sectional view of the ceramic composite coating with partitioned core wire sheet positioning and pore forming according to the present invention. Detailed Implementation
[0052] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments. In the embodiments and comparative examples of this invention, unless otherwise specified, all chemical reagents used were commercially available analytical grade reagents. The process flow diagram for preparing the composite coating of this invention is shown below. Figure 1 As shown. The 45 steel matrix used in the embodiments and comparative examples of this invention is a commercially available product; the auxiliary bonding powder of this invention is only used when the wettability between the ceramic framework phase and the metal outer skin is poor.
[0053] Example 1 A method for preparing a partitioned powder core wire sheet-based porous ceramic composite coating specifically includes the following steps: (1) Using 45 steel as the substrate, the surface of the 45 steel substrate is sandblasted to make the surface roughness Ra of the treated surface 6.3μm, thus obtaining the roughened substrate.
[0054] (2) A tubular NiCr alloy with an outer diameter of 2.0 mm, an inner diameter of 1.50 mm, and a wall thickness of 0.25 mm is used as the conductive metal outer sheath. The tubular NiCr alloy composition includes 80% Ni and 20% Cr by mass percentage. A NiCr alloy isolation sheet with a thickness of 0.10 mm and continuously extending along the axial direction of the wire is set in the inner cavity of the outer sheath (with the same composition as the conductive metal outer sheath). The NiCr alloy isolation sheet is chordally eccentrically set in the cross-section, dividing the inner cavity into two independent powder channels. In the cross-section of the wire, the center line of the NiCr alloy isolation sheet is offset by 0.16 mm relative to the inner cavity center of the tubular NiCr alloy outer sheath towards the sodium chloride template powder channel, so that the ratio of the effective cross-sectional area of the first powder channel to the second powder channel is approximately 65:35. Taking the offset direction of the isolation sheet relative to the inner cavity center as a reference, the larger channel formed on the side of the isolation sheet away from the offset direction is defined as the first channel, and the smaller channel formed on the side of the isolation sheet away from the offset direction is defined as the second channel. The first channel is filled with yttrium-stabilized zirconia powder with a particle size of 15-60 μm, comprising 8% Y₂O₃ and the balance ZrO₂ by mass percentage, purchased from Tianjin Detianzhu Amorphous Nanotechnology Co., Ltd. The second channel is filled with sodium chloride template powder with a particle size of 20-80 μm. The yttrium-stabilized zirconia powder and sodium chloride template powder are filled at a mass ratio of 80:20, with all powders accounting for 25% of the total mass of the partitioned core wire. Before filling, the total mass of the 1m-long tubular NiCr alloy outer sheath and separator is weighed, and the initial mass of the containers holding the two powders and the powders within them is also weighed. After powder filling, outer sheath closure, and sizing, the total mass of the resulting 1m-long partitioned core wire is weighed, and the mass of each container and the remaining powder after filling is also weighed. The difference between the total mass of the partitioned core filament and the total mass of the outer sheath and separator before filling is the actual powder filling mass; the actual filling mass of the two powders is determined based on the corresponding containers and the mass difference before and after powder filling. Upon verification, all powders account for 25% of the total mass of the partitioned core filament, and the mass ratio of yttrium-stabilized zirconia powder to sodium chloride template powder is 80:20, thus obtaining the partitioned core filament.
[0055] (3) The partitioned powder core wire was deposited on the roughened 45 steel substrate surface by arc spraying. The spraying voltage was 34V, the spraying current was 250A, the spraying distance was 150mm, the compressed air pressure was 0.50MPa, and the wire feeding speed was 6.0m / min. During the spraying process, the NiCr alloy outer skin and the separator melted to form a metallic bonding phase. Yttrium oxide stabilized zirconia powder and sodium chloride template powder were deposited together. After deposition, the sodium chloride template powder was at least partially retained at the boundary of the sprayed layer and / or in the local deposition area, forming a ceramic composite deposition layer containing the template phase on the surface of the 45 steel substrate, thus obtaining the sample.
[0056] (4) The sample was placed in deionized water at 60°C and rinsed for 2 hours to selectively dissolve and remove the sodium chloride template phase; then dried at 100°C for 1.5 hours to obtain the coating sample after template removal treatment.
[0057] (5) The coated sample after template removal is placed in an atmosphere furnace and kept at 700℃ for 2 hours in an argon atmosphere with a purity of ≥99.99%. It is then cooled to room temperature in the furnace to obtain a partitioned powder core wire sheet positioning pore ceramic composite coating on the substrate surface.
[0058] Tests showed that the coating prepared in this embodiment includes a yttrium oxide-stabilized zirconia ceramic framework phase, a metal bonding phase formed by a NiCr alloy outer skin and a separator, lamellar positioning pores, and locally interconnected pores. This embodiment achieved the preparation of a lamellar positioning pore-forming ceramic composite coating due to the combined effects of the powder channel position and cross-sectional area ratio, the template powder filling ratio and particle size, the spraying parameters, and the template removal conditions.
[0059] Example 2 A method for preparing a partitioned powder core wire sheet-based porous ceramic composite coating specifically includes the following steps: (1) Using the same 45 steel as in Example 1 as the substrate, the surface of the substrate was sandblasted to make the surface roughness Ra of the treated surface 6.3 μm, and the roughened substrate was obtained.
[0060] (2) A tubular NiCr alloy with an outer diameter of 2.0 mm, an inner diameter of 1.50 mm, and a wall thickness of 0.25 mm is used as the conductive metal outer sheath. The tubular NiCr alloy composition includes 80% Ni and 20% Cr by mass percentage. A NiCr alloy three-cavity partition with a thickness of 0.10 mm and continuously extending along the axial direction of the wire is set in the inner cavity of the outer sheath. The three-cavity partition is composed of three partitions with one end connected to the center of the inner cavity and the other end connected to the inner wall of the tubular NiCr alloy outer sheath. The composition of the partition is the same as that of the conductive metal outer sheath. On the cross-section of the wire, the included angles formed by the center lines of adjacent partitions along the circumferential direction are approximately 198°, 37°, and 125°, respectively. After deducting the cross-sectional area occupied by the partitions, the ratio of the effective cross-sectional areas of the three powder channels is approximately 58:7:35. The channel with a central angle of approximately 198° is defined as the first channel, the channel with a central angle of approximately 37° is defined as the second channel, and the channel with a central angle of approximately 125° is defined as the third channel. The first channel is filled with yttrium-stabilized zirconia powder with a particle size of 15-60 μm, whose composition includes 8% Y₂O₃ and the balance ZrO₂ by mass percentage (purchased from Tianjin Detianzhu Amorphous Nanotechnology Co., Ltd.); the second channel is filled with NiCr auxiliary bonding powder with a particle size of 15-45 μm (the NiCr auxiliary bonding powder consists of 80% Ni and 20% Cr by mass percentage, purchased from Tianjin Detianzhu Amorphous Nanotechnology Co., Ltd.); the third channel is filled with potassium chloride template powder with a particle size of 20-100 μm. The three powders are filled in a mass ratio of 70:10:20 for yttrium-stabilized zirconia powder, NiCr auxiliary bonding powder, and potassium chloride template powder, and the total powder accounts for 3% of the total mass of the partitioned core wire. 0%. Before filling, weigh the total mass of the 1m long tubular NiCr alloy outer skin and the three-cavity partition, and weigh the containers holding the three powders and the initial mass of the powders in them. After powder filling, outer skin closure, and sizing, weigh the total mass of the resulting 1m long partitioned powder core wire, and weigh the mass of each container and the remaining powder after filling. The difference between the total mass of the partitioned powder core wire and the total mass of the outer skin and the three-cavity partition before filling is the actual powder filling mass; the actual filling mass of each powder is determined based on the mass difference of the corresponding container and the powder before and after filling. Upon verification, all powders account for 30% of the total mass of the partitioned powder core wire, and the mass ratio of yttrium oxide stabilized zirconia powder, NiCr auxiliary bonding powder, and potassium chloride template powder is 70:10:20, thus obtaining the partitioned powder core wire.
[0061] (3) The partitioned powder core wire was deposited on the roughened 45 steel substrate surface by arc spraying. The spraying voltage was 36V, the spraying current was 300A, the spraying distance was 180mm, the compressed air pressure was 0.60MPa, and the wire feeding speed was 8.0m / min. During the spraying process, the NiCr alloy outer skin and the three-cavity partition melted and formed a metallic bonding phase together with the NiCr auxiliary bonding powder. Yttrium oxide stabilized zirconia powder and potassium chloride template powder were deposited together. After deposition, the potassium chloride template powder was retained at the boundary of the sprayed layer and / or the local deposition area, forming a ceramic composite deposition layer containing the template phase on the surface of the 45 steel substrate, and the sample was obtained.
[0062] (4) The sample was immersed in deionized water at 50°C and rinsed for 3 hours to selectively dissolve and remove the potassium chloride template phase; then dried at 100°C for 1.5 hours to obtain the coating sample after template removal treatment.
[0063] (5) The coated sample after template removal is placed in an atmosphere furnace and kept at 750°C for 1 hour in an argon atmosphere with a purity of ≥99.99%. The sample is then cooled to room temperature in the furnace to obtain a partitioned powder core wire sheet positioning pore ceramic composite coating on the substrate surface.
[0064] Tests showed that the coating prepared in this embodiment includes a yttrium oxide-stabilized zirconia ceramic framework phase, a metal bonding phase formed by a NiCr alloy outer skin, a three-cavity partition and NiCr auxiliary bonding powder, lamellar positioning pores and locally connected pores. This embodiment achieves the preparation of a lamellar positioning pore-forming ceramic composite coating through the synergistic effect of the powder channel position and cross-sectional area ratio, the template powder filling ratio and particle size, spraying parameters and template removal conditions.
[0065] Example 3 A method for preparing a partitioned powder core wire sheet-based porous ceramic composite coating specifically includes the following steps: (1) Using the same 45 steel as in Example 1 as the substrate, the surface of the substrate was sandblasted to make the surface roughness Ra of the treated surface 5.0 μm, and the roughened substrate was obtained.
[0066] (2) A tubular Ni-5Al alloy with an outer diameter of 1.6 mm, an inner diameter of 0.90 mm, and a wall thickness of 0.35 mm is used as the conductive metal outer sheath. The tubular Ni-5Al alloy comprises 5% Al and the balance Ni by mass percentage. A Ni-5Al alloy isolation sheet with a thickness of 0.10 mm and continuously extending along the axial direction of the wire is set in the inner cavity of the outer sheath. The composition of the isolation sheet is the same as that of the conductive metal outer sheath, and its two sides are connected to the inner wall of the tubular Ni-5Al alloy outer sheath. On the cross-section of the wire, the center line of the isolation sheet is offset by about 0.25 mm relative to the center of the inner cavity towards the sodium sulfate template powder channel. After deducting the cross-sectional area occupied by the isolation sheet, the ratio of the effective cross-sectional areas of the two powder channels formed on both sides of the isolation sheet is about 88:12. The larger channel formed on the side of the isolation sheet away from the offset direction is defined as the first channel, and the smaller channel formed on the side of the isolation sheet away from the offset direction is defined as the second channel. The first channel was filled with gadozirconate powder with a particle size of 5-15 μm and a chemical composition of Gd₂Zr₂O₇, purchased from Tianjin Detianzhu Amorphous Nanotechnology Co., Ltd.; the second channel was filled with sodium sulfate template powder with a particle size of 5-20 μm. The gadozirconate powder and sodium sulfate template powder were filled at a mass ratio of 95:5, with all powder accounting for 15% of the total mass of the partitioned core wire. Before filling, the total mass of the 1m-long tubular Ni-5Al alloy outer sheath and separator was weighed, and the initial mass of the containers holding the two powders and the powders within them was also weighed. After powder filling, outer sheath closure, and sizing, the total mass of the resulting 1m-long partitioned core wire was weighed, and the mass of each container and the remaining powder after filling was also weighed. The difference between the total mass of the partitioned core wire and the total mass of the outer sheath and separator before filling is the actual powder filling mass; the actual filling mass of the two powders is determined based on the mass difference between the corresponding containers and the powder before and after filling. Upon verification, all powder materials account for 15% of the total mass of the partitioned core filament, and the mass ratio of gadozirconate powder to sodium sulfate template powder is 95:5, thus obtaining the partitioned core filament.
[0067] (3) The partitioned powder core wire was deposited on the roughened 45 steel substrate surface by arc spraying. The spraying voltage was 25V, the spraying current was 150A, the spraying distance was 80mm, the compressed air pressure was 0.30MPa, and the wire feeding speed was 2.0m / min. During the spraying process, the Ni-5Al alloy skin and the isolation sheet melted to form a metal bonding phase. Gadolinium zirconate powder and sodium sulfate template powder were deposited together. After deposition, the sodium sulfate template powder was retained at the boundary of the sprayed sheet and / or the local deposition area, forming a ceramic composite deposition layer containing the template phase on the surface of the 45 steel substrate, and the sample was obtained.
[0068] (4) Soak the sample in deionized water at 20°C for 6 hours to selectively dissolve and remove the sodium sulfate template phase; then dry it at 80°C for 2 hours to obtain the coating sample after template removal treatment.
[0069] (5) The coated sample after template removal is placed in an atmosphere furnace and kept at 600℃ for 3 hours in an argon atmosphere with a purity of ≥99.99%. It is then cooled to room temperature in the furnace to obtain a partitioned powder core wire sheet positioning pore ceramic composite coating on the substrate surface.
[0070] Tests showed that the coating prepared in this embodiment includes a gadozirconate ceramic framework phase, a metallic bonding phase formed by a Ni-5Al alloy outer skin and a separator, lamellar positioning pores, and locally interconnected pores. This embodiment achieved the preparation of a lamellar positioning and pore-forming ceramic composite coating through the combined effects of the powder channel position and cross-sectional area ratio, the template powder filling ratio and particle size, spraying parameters, and template removal conditions.
[0071] Example 4 A method for preparing a partitioned powder core wire sheet-based porous ceramic composite coating specifically includes the following steps: (1) Using the same 45 steel as in Example 1 as the substrate, the surface of the substrate was sandblasted to make the surface roughness Ra of the treated surface 10.0 μm, and the roughened substrate was obtained.
[0072] (2) A tubular FeCrAl alloy with an outer diameter of 2.4 mm, an inner diameter of 2.10 mm, and a wall thickness of 0.15 mm is used as a conductive metal outer sheath. The tubular FeCrAl alloy composition includes 20% Cr, 5% Al, and the balance Fe by mass percentage. A FeCrAl alloy isolation tube with an inner diameter of 1.27 mm, an outer diameter of 1.47 mm, and a wall thickness of 0.10 mm is coaxially arranged in the inner cavity of the conductive metal outer sheath and extends continuously along the axial direction of the wire. The composition of the isolation tube is the same as that of the conductive metal outer sheath, thereby forming an inner powder channel and an outer annular powder channel. After deducting the cross-sectional area occupied by the isolation tube wall, the effective cross-sectional area ratio of the inner powder channel to the outer annular powder channel is approximately 42:58. The inner channels were filled with ytterbium silicate powder with a particle size of 60-100 μm and a chemical composition of Yb₂Si₂O₇, purchased from Tianjin Detianzhu Amorphous Nanotechnology Co., Ltd.; the outer annular channels were filled with potassium sulfate template powder with a particle size of 80-150 μm. The ytterbium silicate powder and potassium sulfate template powder were filled at a mass ratio of 55:45, with all powders accounting for 35% of the total mass of the partitioned core wire. Before filling, the total mass of the 1m-long tubular FeCrAl alloy outer sheath and the isolation tube was weighed, and the initial mass of the containers holding the two powders and the powders within them was also weighed. After powder filling, outer sheath closure, and sizing, the total mass of the resulting 1m-long partitioned core wire was weighed, and the mass of each container and the remaining powder after filling was also weighed. The difference between the total mass of the partitioned core wire and the total mass of the outer sheath and isolation tube before filling is the actual powder filling mass; the actual filling mass of the two powders is determined based on the mass difference between the corresponding containers and the powder before and after filling. Upon verification, all powder materials account for 35% of the total mass of the partitioned core filament, and the mass ratio of ytterbium silicate powder to potassium sulfate template powder is 55:45, thus obtaining the partitioned core filament.
[0073] (3) The partitioned powder core wire was deposited on the roughened 45 steel substrate surface by arc spraying. The spraying voltage was 45V, the spraying current was 450A, the spraying distance was 250mm, the compressed air pressure was 0.80MPa, and the wire feeding speed was 12.0m / min. The FeCrAl alloy outer skin and the isolation tube melted to form a metallic bonding phase. Ytterbium silicate powder and potassium sulfate template powder were deposited together. After deposition, the potassium sulfate template powder was retained at the boundary of the sprayed layer and / or the local deposition area, forming a ceramic composite deposition layer containing the template phase on the surface of the 45 steel substrate, and the sample was obtained.
[0074] (4) Place the sample in deionized water at 80℃ and wash it at an ultrasonic frequency of 40kHz for 0.5h to selectively dissolve and remove the potassium sulfate template phase; then dry the sample at 120℃ for 1h to obtain the coating sample after template removal treatment.
[0075] (5) The coated sample after template removal is placed in an air atmosphere furnace and kept at 900℃ for 0.5h. It is then cooled to room temperature with the furnace to obtain a partitioned powder core wire sheet positioning pore ceramic composite coating on the substrate surface.
[0076] Tests showed that the coating prepared in this embodiment includes a ytterbium silicate ceramic framework phase, a metal bonding phase formed by the FeCrAl alloy outer skin and the isolation tube, lamellar positioning pores and locally connected pores. This embodiment achieves the preparation of a lamellar positioning pore-forming ceramic composite coating by the effect of the powder channel position and cross-sectional area ratio, the template powder filling ratio and particle size, the spraying parameters and the template removal conditions.
[0077] Comparative Example 1 This comparative example uses the same 45 steel substrate, powder type, total powder filling rate, and post-treatment conditions as Example 1. The only difference is that no isolation structure is set. Instead, yttrium-stabilized zirconia powder and sodium chloride template powder are mixed at a mass ratio of 80:20 and filled into the same powder core area to obtain a non-partitioned powder core wire. Subsequently, a ceramic composite coating is prepared according to the arc spraying, circulating rinsing, drying, and stabilization heat treatment conditions of Example 1.
[0078] Analysis of the feeding method and hole formation mechanism shows that the two powders in Comparative Example 1 are directly mixed in the same powder core area. The template powder lacks a relatively independent feeding path before entering the arc spraying area, and its deposition distribution is more easily affected by the powder mixing state, wire feeding disturbance and the deposition state of sprayed particles. After being removed by the water medium, it is not conducive to the stable formation of the sheet positioning pores and local interconnected holes corresponding to the sprayed sheet structure.
[0079] In contrast, the embodiments of the present invention, by dividing the cross-section and extending each powder channel continuously along the axial direction of the wire, ensure that different powders remain physically separated before entering the arc spraying zone; after the template phase is positioned, retained, and subsequently selectively removed, it is more conducive to making the pore formation location correspond to the sprayed sheet structure. The pore formation process of the embodiments of the present invention is achieved by the selective removal of the water-soluble inorganic salt template phase, rather than by the volatilization of the conductive metal outer layer to form pores.
[0080] The above embodiments are used to illustrate the technical solution of the present invention and do not limit the scope of protection of the present invention. Without departing from the technical concept of the present invention, those skilled in the art can make corresponding adjustments to the material types, partition structures, and process parameters.
Claims
1. A method for preparing a partitioned powder core wire sheet-based porous ceramic composite coating, characterized in that, Specifically, the following steps are included: (1) The surface of the substrate is roughened to obtain the roughened substrate; (2) Using tubular conductive metal as the outer sheath of partitioned powder core wire, an isolation structure is set in the inner cavity of the tubular conductive metal outer sheath, extending continuously along the axial direction of the partitioned powder core wire, and independent powder channels are formed in the cross-sectional direction of the inner cavity of the tubular conductive metal outer sheath. Ceramic skeleton powder, water-soluble inorganic salt template powder, and auxiliary bonding powder are filled into different powder channels respectively to obtain partitioned powder core wire. (3) The partitioned powder core wire is deposited on the roughened substrate surface by electric arc spraying to form a ceramic composite deposition layer containing template phase; (4) Selective template removal treatment of the ceramic composite deposition layer containing template phase is carried out in aqueous medium to obtain the ceramic composite deposition layer after selective template removal treatment; (5) The ceramic composite deposition layer after selective template removal is subjected to stabilization heat treatment to obtain a partitioned powder core wire sheet positioning pore ceramic composite coating on the substrate surface.
2. The method for preparing a partitioned powder core wire sheet-type pore-forming ceramic composite coating according to claim 1, characterized in that, The outer diameter of the tubular conductive metal outer sheath in step (2) is 1.6~2.4mm and the wall thickness is 0.15~0.35mm; the tubular conductive metal outer sheath is one of Ni-based alloy, Fe-based alloy, Co-based alloy, stainless steel, NiCr alloy, FeCrAl alloy or NiAl alloy.
3. The method for preparing the partitioned powder core wire sheet positioning and pore-forming ceramic composite coating according to claim 1, characterized in that, The isolation structure in step (2) is one or more of the following: isolation sheet, isolation rib, isolation tube, multi-cavity partition or rolled partition wall; the isolation structure is made of the same alloy as the tubular conductive metal outer skin, or is made of a metal or alloy that is metallurgically compatible with the tubular conductive metal outer skin.
4. The method for preparing a partitioned powder core wire sheet-type pore-forming ceramic composite coating according to claim 1, characterized in that, In step (2), there are 2 or 3 powder channels. When there are 2 powder channels, the 2 powder channels are filled with ceramic skeleton powder and water-soluble inorganic salt template powder, respectively. When there are 3 powder channels, the 3 powder channels are filled with ceramic skeleton powder, auxiliary binding powder and water-soluble inorganic salt template powder, respectively.
5. The method for preparing a partitioned powder core wire sheet-type pore-forming ceramic composite coating according to claim 4, characterized in that, When two powder channels are set in step (2), the filling powder is composed of ceramic skeleton powder and water-soluble inorganic salt template powder in a mass ratio of 95:5 to 55:
45. When three powder channels are set, the filling powder is composed of ceramic skeleton powder, auxiliary bonding powder and water-soluble inorganic salt template powder in a mass ratio of 70:10:
20. The total mass of the filling powder accounts for 15% to 35% of the total mass of the partitioned core wire, and the remaining mass is composed of tubular conductive metal outer skin and isolation structure. The particle size of the ceramic skeleton powder is 5 to 100 μm. The particle size of the water-soluble inorganic salt template powder is 5 to 150 μm.
6. The method for preparing a partitioned powder core wire sheet-type pore-forming ceramic composite coating according to claim 1, characterized in that, The ceramic skeleton powder in step (2) is one or more of the following: zirconium oxide-based ceramics, rare earth zirconate ceramics, rare earth silicate ceramics, mullite, chromium oxide-based ceramics, or titanium oxide-based ceramics; the water-soluble inorganic salt template powder is one or more of the following: sodium chloride, potassium chloride, sodium sulfate, or potassium sulfate.
7. The method for preparing a partitioned powder core wire sheet-based porous ceramic composite coating according to claim 1, characterized in that, The conditions for arc spraying in step (3) are: spraying voltage of 25~45V, spraying current of 150~450A, spraying distance of 80~250mm, compressed gas pressure of 0.3~0.8MPa, and wire feeding speed of 2~12m / min.
8. The method for preparing a partitioned powder core wire sheet-type pore-forming ceramic composite coating according to claim 1, characterized in that, The selective template removal process of the aqueous medium in step (4) is one or a combination of aqueous medium soaking, aqueous medium circulation rinsing, aqueous medium ultrasonic assisted elution, or aqueous medium flow elution; the temperature of the selective template removal process is 20~80℃ and the time is 0.5~6h.
9. The method for preparing a partitioned powder core wire sheet-type pore-forming ceramic composite coating according to claim 1, characterized in that, The stabilization heat treatment conditions in step (5) are: stabilization heat treatment at 600~900℃ for 0.5~3h.
10. The partitioned powder core wire sheet positioning porous ceramic composite coating prepared by the method according to any one of claims 1 to 9, characterized in that, The ceramic composite coating includes a ceramic skeleton phase, a metal bonding phase formed by a tubular conductive metal outer skin, an isolation structure, and auxiliary bonding powder, as well as lamellar positioning pores and locally connected pores. The lamellar positioning pores are formed by selective removal of a water-soluble inorganic salt template phase through an aqueous medium and are distributed at the boundaries of the sprayed lamellar layers and / or in local deposition areas. The locally connected pores are formed by connecting adjacent lamellar positioning pores.